Preventive Detention: Needs and Challanges - Khandelwal, Charchit; Jain, Mayank; Singhal, Deepak (International Journal of Law, Human Rights and Constitutional Studies; Vol 2 No 1 (2020): International Journal of Law, Human Rights and Constitutional Studies, 2020)
Preventive Detention is basically, an action taken before to prevent the possible commitment of the subsequent crime. Preventive Detention thus is an action taken on suspicion that some wrong would be committed by the person. It can be made on certain grounds security of state, maintenance of peace etc. A person may be detained without any trail on any of the above grounds. In India, The detention process can’t go beyond 3 months else it needs to be presented to the advisory board. Preventive Detention laws can be made both at central as well as state levels. This paper examines the needs and challenges of Preventive Detention. To analyze this concept, this paper uses a textual and structural analysis on article 22 and certain laws made under this concept. This paper will also provide the comparison between Preventive Detention Laws in India and Preventive Detention Laws in other countries. The paper will propose certain possible ways to fill the gap prevailing in Indian law.